Archival Type Bastards - Panayides, Omiros (My University, 2026)
“Archival Type Bastards” is a collection of mashed-up typographic collages, featuring book titles that were found on the covers of literature and poetry books in Cyprus, sourced from the online archive “Books, Type, and Cyprus.”